ChemInform Abstract: The Ketene‐Surrogate Coupling: Catalytic Conversion of Aryl Iodides into Aryl Ketenes Through Ynol Ethers. Issue 6 (23rd January 2015) - Zhang, Wenhan; Ready, Joseph M.
Abstract Compounds (I) are transformed to ketene intermediates via a Sonogashira coupling.